Associação entre níveis de pressão arterial e letalidade na fase aguda do acidente vascular cerebral: estudo prospectivo - Furlan, Natalia Eduarda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objective: Investigating the association between blood pressure (BP) and lethality in stroke in the acute phase, in patients in intensive care units (ICU) of a university hospital. Methods: It is a prospective trial. This study has analyzed patients older than 18 years and of both sexes, admitted in the ICU with a diagnosis of hemorrhagic and ischemic stroke. It has excluded patients with subarachnoid hemorrhage. We have evaluated the APACHE II index, the modified Rankin scale, the international scale of the accident stroke of the National Institute of Health (NIHSS) (NIH, 2009) and the value of BP at admission of patients, as well during their first week, clinical and laboratory data. The primary outcome was death, from all causes, in the first seven days and the secondary endpoints were death from neurological and non-neurological causes during the same period. Results: The study analyzed 146 patients, the average age was 66.3 ± 13,4 years, 56.1% of patients were male, the predominant race was the white, in 89% of analyzed, ischemic form of the disease affected 69 1% of patients. Among all patients 80.1% were hypertensive and the average value of NIHSS score was 16.4 ± 6,5 points. Patients with PA, on arrival and in the first 48 hours of admission, with values below 140 mm Hg had higher chance of death. This association was observed only on the non-neurological origin of death, and it showed marginal statistical significance in the multivariate analysis, adjusted for NIHSS, type of stroke, BP variability, variability of blood glucose, thrombolysis, occurrence of infection and creatinine. Since the BP variability, showed a statistically significant association with the primary outcome, independent of confounders evaluated. Conclusion: There was a negative association between PA and mortality of stroke in the acute phase in patients in intensive care units. This association was present only for ...

Objetivo: Verificar a associação entre pressão arterial (PA) e letalidade do Acidente Vascular Cerebral (AVC), na fase aguda, em pacientes internados nas unidades de terapia intensiva (UTIs) de um hospital universitário. Métodos: Estudo observacional e prospectivo. Foram analisados pacientes com idade superior a 18 anos e de ambos os sexos, internados nas UTIs com diagnóstico de AVC hemorrágico e isquêmico. Foram excluídos os portadores de hemorragia subaracnóidea. Foram avaliados o índice APACHE II, a escala de Rankin modificada, a escala internacional de AVC do National Institute of Health (NIHSS) (NIH, 2009) e o valor da PA no momento da internação dos pacientes, bem como durante toda primeira semana, além de dados clínicos e laboratoriais. O desfecho primário foi o óbito, por todas as causas, nos primeiros sete dias e os secundários foram o óbito por causa neurológica e o óbito por causa não neurológica, no mesmo período. Resultados: Foram analisados 146 pacientes, a média de idade foi de 66,3± 13,4 anos, 56,1% dos pacientes foram do sexo masculino, a raça predominante foi a branca, em 89% dos analisados, a forma isquêmica da doença acometeu 69,1% dos pacientes. Dentre todos os pacientes 80,1% eram hipertensos e o valor médio do escore NIHSS foi de 16,4 ± 6,5 pontos. Pacientes que apresentaram PA, na admissão e nas primeiras 48 horas de internação, com valores abaixo de 140 mm Hg apresentaram maior chance de óbito. Essa associação foi observada apenas quanto ao óbito de origem não neurológica, bem como apresentou significância estatística marginal na análise múltipla, com ajuste para o NIHSS, tipo de AVC, maior variabilidade da PA, variabilidade da glicemia, realização de trombólise, ocorrência de infecção e creatinina. Já a variabilidade da PA, apresentou associação estatisticamente significante com o desfecho primário, independente dos fatores de confusão avaliados. Conclusão: Houve...
The relationship between blood pressure and mortality in stroke: prospective study
Keywords: Acidente vascular cerebral; Tratamento intensivo; Hipertensão; Mortalidade; Cerebrovascular disease; Hypertension